Transcriptional Regulation of Vih by Oct4 and Sox9 in Scylla paramamosain - Liao, Jiaqian; Zhang, Ziping; Jia, Xiwei; Zou, Zhihua; Liang, Keying; Wang, Yilei (Frontiers in Endocrinology, 2020)
Mud crab (Scylla paramamosain) is one of the most economically-important marine crabs in China. However, research on mechanisms of reproductive regulation is not sufficient. Vitellogenesis-inhibiting hormone (VIH) is a member of the crustacean hyperglycemia hormones (CHH) family, which plays an essential role in the regulation of gonadal development and maturation in crustaceans, and current studies on the regulation of Vih transcription in crabs are relatively rare. Our previous studies on the transcriptional regulation of mud crab Vih (SpVih) have proved that the binding site of Oct4/Sox9 transcription factor may be the key region for positively regulating the expression of SpVih. In this study, the electrophoretic mobility shift assay (EMSA) experiment confirmed that the nuclear protein extracted from the eyestalk could bind to the key region of SpVih promoter, and these specific bindings were dependent on the presence of Oct4/Sox9 binding sites. Two specific binding complex bands were detected in the supershift group of EMSA supershift experiments by Oct4 and Sox9 antibodies, further confirming the specific recognition of these two transcription factors on the key regulatory region of SpVih. In vitro, Oct4 and Sox9 gene overexpression vectors and SpVih core promoter fragment vector were constructed and co-transfected into HEK293T cells. As a result, SpVih activity increased with the concentration of transcription factors. In vivo, when Oct4 and Sox9 dsRNA were injected into the eyestalks of mud crab, respectively, the expression level of SpVih decreased significantly after interference with Oct4 or Sox9, and the expression level of SpVtg in the ovary and hepatopancreatic increased. Both in vitro and in vivo experiments showed that Oct4 and Sox9 had a positive regulatory effect on SpVih. The GST pull-down experiment was carried out by purified Oct4 and Sox9 proteins, and the results showed that there was an interaction between them. It was speculated that they regulated the expression of SpVih through the interaction.